Unpredictable Sharing Economy: Barbaric Growth, Deceptive Representation and Divergent Regulation - Xie Xinshui; Liu Xiaotian (Contemporary Social Sciences, 2017)
In the context of globalization and informatization, some traditionally lowtech and labor-intensive sectors have developed mobile Internet-based platforms and formed a new business format: the sharing economy. In the beginning, such a new business format lowered the threshold of participation, cut dealing costs, and enjoyed the relative advantage of being free from regulatory institutions. Therefore, it easily attracted investments and witnessed rapid development. Early-stage of the sharing economy features were “being shared, collaborative and on-demand.” For a variety of reasons, the development of the sharing economy has already been accepted and recognized by current society. It is expected to become a new growth point and has the chance to replace the established business format of our industrial society and subsequently trigger many more “pain points.” Regarding the regulation and governance of the sharing economy, there are divergences in its legality, platform nature, industrial impact and employment relationships. Identifying and resolving such regulatory divergences to the maximum degree is a prerequisite for the governance of the sharing economy and also a key to its smooth development